Molecular Investigation of E.dispar in Terms of Virulence Factors CP1, CP5 - Khalid Thamir Mattar AL-Shaibani (Journal of Global Pharma Technology, 2018)
The current study included the detection of  existence the Parasite E.dispar in 180  samples of feces  for  stricken patients with diarrhea from revisers  to  public hospital of Al -Shamia  and three primary health centers in the district of Al- Shamia which is subsidiary to Al- Qadisiyah governorate  for period of  July 2016 till the end of December 2017, only 48 samples containing the Parasite of amoeba with it nourished  ,sacked  state  or both out of 180 sample of  feces for stricken   patients with diarrhea, the incidence rate of the Parasite of amoeba recorded 26.22%, and the obligation results are submitted to microscopic examination for  Molecular examination  to Real Time PCR (Taq Man Probe) to specific  investigate  to the   E. dispar and indicate the existence this kind in 31 samples ,with  64.58% rate  of the total of 48 obligation samples, after then the obligation samples  underwent to  molecular testing for E. dispar to investigate  about each of  the two the predation virulence factors, CP1 and CP5 using SYBER Green Real Time PCR. the current study has shown that  the possession E. dispar  for the virulence factors malign factor  of CP1 using  the initiators  concern the genes,  then proved existence of the CP1 factor  in  18 samples of total  31 positive   samples for parasite with 58.06% rate . While did not prove existence the gene of the CP5 in the type of E. dispar. Some studies to be positive about  that E. dispar coexisted  in the intestines  of human , while other studies pointed to a lack of clarity about the  fact  of  this type has   pathogen or no , because of  its ability to bring about (causation ) some focal lesions and harming  and make damage in the laboratory  living tissues . from this standpoint, the current study  come to investigate about two virulence factors of the virulence factors   as a step  of steps the  study  which consider the most comprehensive study of the Species E. dispar to show  the reality of living of this kind.Keywords: E. dispar, CP1, CP5.